Microbiological Quality of Eye Cosmetics - สายรวมญาติ , สิริมา; ไทยตระกูลพาณิช , สิรินันท์; เธียรอังกูร , สุวรรณา (Journal of Health Science of Thailand, 2021)
The microbiological quality of 265 eye cosmetic products has been analyzed by the Division of Cosmetics and Hazardous Substances between July 2004 and February 2006. According to the criteria set by the Thai Industrial Standard for cosmetics, TIS 152-1996, 13 samples (4.9%) did not meet the microbiological requirements. It was found that the 8 samples of imported powder eye shadows, were contaminated and negatively became the most prominent, followed by 2 samples contaminated Thai eye cream and gel. Other contaminated samples were detected from 2 liquid eyeliners and 1 mascara which contained no details of the producers. Clostridium perfringens and Clostridium spp. were the most frequently identified in the contaminated products. In addition, the high level of contamination-105 cfu/g-and the specified micro-organisms as Pseudomonas aeruginosa and Streptococcus casseliflavus were found in 1 liquid eyeliner. Since the eye cosmetic products are used around the eye area, and, therefore, presents a high risk of microbial infection. Eye infections, particularly with Clostridium, can become critical leading to loss of visual function and loss of the eye globe. Therefore consumers must pay special attention in purchasing and using eye cosmetic products.